VD_FINDINFO HC / 2012 / 150 vom 2. Januar 2012 - VD Tribunal cantonal (2012)
COPROPRIÉTÉ, CONTRIBUTION AUX FRAIS D'ADMINISTRATION, APPRÉCIATION DES PREUVES | 649 al. 1 CC, 649 al. 2 CC, 308 CPC (CH), 310 CPC (CH), 311 CPC (CH), 405 CPC (CH)